Does It Pay Off to Explicitly Link Functional Gene Expression to Denitrification Rates in Reaction Models? - Störiko, Anna; Pagel, Holger; Mellage, Adrian; Cirpka, Olaf A. (Frontiers in Microbiology, 2021)
Environmental omics and molecular-biological data have been proposed to yield improved quantitative predictions of biogeochemical processes. The abundance of functional genes and transcripts relate to the number of cells and activity of microorganisms. However, whether molecular-biological data can be quantitatively linked to reaction rates remains an open question. We present an enzyme-based denitrification model that simulates concentrations of transcription factors, functional-gene transcripts, enzymes, and solutes. We calibrated the model using experimental data from a well-controlled batch experiment with the denitrifier Paracoccous denitrificans. The model accurately predicts denitrification rates and measured transcript dynamics. The relationship between simulated transcript concentrations and reaction rates exhibits strong non-linearity and hysteresis related to the faster dynamics of gene transcription and substrate consumption, relative to enzyme production and decay. Hence, assuming a unique relationship between transcript-to-gene ratios and reaction rates, as frequently suggested, may be an erroneous simplification. Comparing model results of our enzyme-based model to those of a classical Monod-type model reveals that both formulations perform equally well with respect to nitrogen species, indicating only a low benefit of integrating molecular-biological data for estimating denitrification rates. Nonetheless, the enzyme-based model is a valuable tool to improve our mechanistic understanding of the relationship between biomolecular quantities and reaction rates. Furthermore, our results highlight that both, enzyme kinetics (i.e., substrate limitation and inhibition), and gene expression or enzyme dynamics are important controls on denitrification rates.